Akbar and the crows and other stories level 5 - Horsburgh, Nicholas (Karachi : Oxford university press, 2023)
"Akbar and the Crows and Other Stories" (Level 5, Oxford) is a collection of fascinating tales from the Indian subcontinent, featuring Emperor Akbar and his wise advisor Birbal. In the title story, Akbar faces a challenge with crows in his kingdom and seeks Birbal$1 (Bs clever solution, highlighting Birbal's wit and intelligence. Other stories in the collection explore themes of wisdom, justice, and problem-solving, with a focus on clever solutions to difficult situations. The book is written in simple language suitable for level 5 readers and offers valuable lessons through entertaining narratives.s
Keywords: English : Short stories; Oxford : Level 5